Survival-of-the-fittest: embracing change through enhanced supply chain resilience capabilities / Ainul Haniza Mohd Rashid and Noorain Omar - Mohd Rashid, Ainul Haniza; Omar, Noorain (Universiti Teknologi MARA, Kedah, 2019)
Change is inevitable in today’s interconnected, volatile, global economy and high-risk world, where supply chains have become increasingly vulnerable to disruptions caused by natural and man-made events. Resilience is a dynamic capability that emphasizes the ability of an enterprise to embrace and respond to change. However, organizations tend to become less resilient as they grow more complex. Hence, they must learn when to anticipate, absorb and overcome disruptions since one-sizefits- all is not an effective approach to managing supply chains. Supply chain management literature suggests that organizational resilience can be cultivated by understanding their supply chain vulnerabilities and by developing specific managerial capabilities to cope with unpredictable disruptions more effectively than their competitors. Thepurpose of this article is to review and identify the capabilities needed by organizations from contingent and resource-based perspectives. The electronics industry in Malaysia is still highly dependent on sourcing electrical parts from the USA, Japan, China and Thailand although being natural disaster-prone countries. This study will provide important implications for the management in this industry to develop a portfolio of capabilities to address important resilient gaps and thus strengthen overall competitiveness. Supply chain resilience strategies can proactively assist in managerial decision-making under uncertainty, with risk so as to understand how (and if) supply chains can return to an original or different functioning state, for business continuity and survival.